2010
DOI: 10.1507/endocrj.k09e-046
|View full text |Cite
|
Sign up to set email alerts
|

Shifts in Diet from High Fat to High Carbohydrate Improved Levels of Adipokines and Pro-inflammatory Cytokines in Mice Fed a High-fat Diet

Abstract: Abstract. High-fat diets induce an expansion of the adipose tissue (aT) that can be characterized by chronic low-grade inflammation. AT is an important source of adipokines and pro-inflammatory cytokines. The purpose of this study was to evaluate the effects of a shift from a high-fat diet to high-carbohydrate (CHO) diet on the blood levels of adipokines and pro-inflammation cytokines in mice fed a high-fat diet. Six-week-old male C57BL/6 mice were fed a high-fat diet (40% of the total calories) for 9 weeks to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
31
1
1

Year Published

2011
2011
2019
2019

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 61 publications
(36 citation statements)
references
References 41 publications
3
31
1
1
Order By: Relevance
“…On the other hand, inflammatory cytokines such as TNF-a and IL-6 may also cause dysfunction of peripheral insulin receptor and insulin resistance and ultimately increase glucose concentrations in plasma (88,89). A high-fat diet increased inflammatory cytokines and caused insulin resistance and hyperglycemia (90,91). The hypoglycemic effect of naringin is well documented ( Table 4) (80,92).…”
Section: Effect Of Naringin On Hyperglycemia and Diabetesmentioning
confidence: 99%
“…On the other hand, inflammatory cytokines such as TNF-a and IL-6 may also cause dysfunction of peripheral insulin receptor and insulin resistance and ultimately increase glucose concentrations in plasma (88,89). A high-fat diet increased inflammatory cytokines and caused insulin resistance and hyperglycemia (90,91). The hypoglycemic effect of naringin is well documented ( Table 4) (80,92).…”
Section: Effect Of Naringin On Hyperglycemia and Diabetesmentioning
confidence: 99%
“…Indeed, a study carried out in mice revealed that the inflammatory state associated with obesity appears to be partly triggered by high fat diet and excessive weight [22]. Furthermore, the composition and quantity of the fat content of a meal seems to be directly related to the magnitude of the postprandial inflammatory response [23].…”
Section: Introductionmentioning
confidence: 99%
“…C57BL/6 mice fed a HFD develop progressive insulin resistance and provide a good model for studying obesity-related hyperinsulinemia (55). After mice receive a HFD for 3 mo, there is an approximately twofold increase in plasma insulin, which is much more akin to the changes found in human obesity than those seen in ZO rats (24,55). Administration of a HFD also produces hyperlipidemia, hyperleptinemia, and hypoadiponectinemia in C57BL/6 mice, thereby mimicking the changes seen with metabolic syndrome in humans (24).…”
mentioning
confidence: 99%